THE EFFECT OF CONSUMING CELERY-CARROT PUDDING ON THE CHOLESTEROL LEVEL OF HYPERCOLESTEROLEMIA IN ASPOL KOBLEN BUBUTAN SURABAYA - Merina Widyastuti (UNEJ e-Proceeding, 2017)
Background: Hypercholesterolemia is a common clinical situation that lipoprotein meatbolic disorder characterized by elevated serom low density lipoprotein and blood cholesterol and conidered as one of the significant important risk factors of atherosclerosis that leads to cardiovascular diseases. Prevention and relapse of such circumstances depends on diet and cholesterol control. One of the most effective herbal therapies is the consumption of celery and carrots in attempts to controll cholesterol levels. This study aims to analyze the effect of giving celery-carrot pudding on cholesterol level changes in patients with hypercholesterolemia in Aspol Koblen Bubutan Surabaya. Methods: Pre experimental research design with one group pretest-posttest design. Sample Population of hypercholesterolemia patient Aspol Koblen Bubutan Surabaya with sample number 17 respondents selected by non probability sampling approach. The research instrument used cholesterol observation sheet. Data were analyzed by using paired t test. Results: The results described average cholesterol levels 257 mg / dl before treatment and after treatment to 204 mg / dl. The result of paired t test showed the effect of giving celery combination of carrot pudding to cholesterol level change with p <0.001 (p <0.05). Conclusion: The implication of this research is celery-carrot pudding could decline lower cholesterol level in hypercholesterolemia patient, so for hypercholesterolemia patient should consume celery-carrot pudding as one of non pharmacologic treatment to decrease cholesterol level. Keywords: hypercholesterolemia, celery pudding, carrots.